Thoracic mucormycosis in immunocompetent patients. Issue 4 (19th January 2021) - Panchanatheeswaran, Karthik; Ram, Duvuru; Prasad, Sreevathsa; Srinivas, Bheemanathi Hanuman; Rath, Durgaprasad; SaiChandran, Bathal Vedagiri; Munuswamy, Hemachandren
Abstract: Background: Mucormycosis is an invasive fungal infection. It is rare and commonly associated with fatal outcomes. Methods: We report two cases of thoracic mucormycosis in immunocompetent patients. First, is an immunocompetent child with mediastinal mass and extension into the pericardium and left atrium. The second is a young woman with a left pulmonary artery pseudoaneurysm. Results: The first patient could not be salvaged while the second patient was successfully managed with surgical intervention and systemic antifungal treatment. Conclusion: Mucormycosis should be considered as a differential diagnosis in the management of immunocompetent patients in patients with pyrexia of unknown origin and a mediastinal mass. Early and aggressive surgical management along with systemic antifungal treatment improves the survival in this subset of patients.